Discovering the Core of the Russian Interbank Market - Sluiskes, Marije (Student Undergraduate Research E-journal!, 2018)
This paper investigates to what extent the structure of the Russian interbank market over the period 1998-2004 can be described by applying the core-periphery model as defined by Craig and von Peter (2014), using a greedy algorithm. It finds that the fit is significant, although the error score of 54 percent is relatively high compared to earlier studies which applied this core-periphery model to more mature interbank markets. Additionally, this paper finds that the fit of the core-periphery model deteriorates as loan maturity increases. Finally, this paper concludes that a bank can also be classified as belonging to the core by doing a probit regression on a single balance sheet variable.